A New Photocatalytic System Using Steel Mesh and Cold Cathode Fluorescent Light for the Decolorization of Azo Dye Orange G. (8th August 2012) - Chang, Ming-Chin; Huang, Chin-Pao; Shu, Hung-Yee; Chang, Yung-Chen
Abstract : High color and organic composition, the effluents from the textile dyeing and finishing industry, can be treated by photocatalytic oxidation with UV/TiO2 . The objective of this study was to prepare a new photocatalytic system by coating nanosized TiO2 particles on steel mesh support and using cold cathode fluorescent light (CCFL) irradiation at 365 nm in a closed reactor for the oxidation of azo dye C.I. Orange G (OG). Various factors such as reaction time, coating temperature, TiO2 dosage, pH, initial dye concentration, and service duration were studied. Results showed efficient color removal of the OG azo dye by the photocatalytic system with TiO2 -coated temperature at 150°C. The optimal TiO2 dosage for color removal was 60 g m −2 . An acidic pH of 2.0 was sufficient for photocatalytic oxidation whereas basic condition was not. The rate of color removal decreased with increase in the initial dye concentration. The TiO2 -coated steel mesh can be used repeatedly over 10 times without losing the photocatalytic efficiency. Results of FTIR and IC indicated the breakage of N=N bonds, with sulfate as the major and nitrite and nitrate as the minor products, which implied degradation of dye molecules.